Judging trustworthiness from faces: Emotion cues modulate trustworthiness judgments in young children. (23rd October 2015) - Caulfield, Frances; Ewing, Louise; Bank, Samantha; Rhodes, Gillian
Abstract : By adulthood, people judge trustworthiness from appearances rapidly and reliably. However, we know little about these judgments in children. This novel study investigates the developmental trajectory of explicit trust judgments from faces, and the contribution made by emotion cues across age groups. Five‐, 7‐, 10‐year‐olds, and adults rated the trustworthiness of trustworthy and untrustworthy faces with neutral expressions. The same participants also rated faces displaying overt happy and angry expressions, allowing us to investigate whether emotion cues modulate trustworthiness judgments similarly in children and adults. Results revealed that the ability to evaluate the trustworthiness of faces emerges in childhood, but may not be adult like until 10 years of age. Moreover, we show that emotion cues modulate trust judgments in young children, as well as adults. Anger cues diminished the appearance of trustworthiness for participants from 5 years of age and happy cues increased it, although this effect did not consistently emerge until later in childhood, that is, 10 years of age. These associations also extended to more subtle emotion cues present in neutral faces. Our results indicate that young children are sensitive to facial trustworthiness, and suggest that similar expression cues modulate these judgments in children and adults.